Explaining (non) participation in overseas voting: the case of overseas Filipino voters in Japan in the 2016 elections. Issue 1 (2nd January 2021) - Jaca, Georgeline B.; Torneo, Ador R.
ABSTRACT: This study explains the low Overseas Voting (OV) participation among Filipino migrants, by examining OV in Japan in the 2016 elections. Feddersen and Sandroni's ([2006]. "A Theory of Participation in Elections." American Economic Review 96 (4): 1271–1282. doi:10.1257/aer.96.4.1271) rational model of electoral participation is adopted to produce evidence-based claims on why OV among Filipino migrants in Japan is low. By examining the perceived benefits, costs, and sense of citizen duty of the overseas Filipinos vis-à-vis their physical absence from their (imagined) homeland, this study shows that voting costs overwhelm the benefits of voting and migrants tend to exercise their citizenship through other means. The low electoral participation of overseas Filipinos is not a manifestation of the loss of allegiance to the homeland nor political disinterest. Rather, voting is not seen as an urgent need nor a responsibility as an overseas national, albeit acknowledged as a civic duty. These have important implications for improving OV participation among Filipinos and other diaspora communities that chronically have low electoral participation.